The principles and practice of bar and beverage management the drinks handbook - Murphy, James (Goodfellow Publishers Ltd., 2013)
A comprehensive training guide and authoritative resource essential for all students, bartenders, sommeliers, mixologists, waiters and food and beverage practitioners the world over. It provides an in-depth knowledge of the products, plus the technical skills, practices and latest developments in the bar and beverage area.